Pembaharuan Islam di India - Hamid, Nirwan (Universitas Islam Negeri Raden Intan Lampung, 2016)
Movement and renewal undertaken by the figures of Islam are a proof that Islam is not only able to transform it into a force that can‟t see just one eye but also is assimilated with the local cultural products does not eliminate the Islamic identity for the sake of building a nation.Muslim leaders are able to evoke the spirit of Islam in an effort to reunite his country which has been monopolized by foreign parties. And with brilliant ideas that these leaders are able to restore confidence in them each to defend their country of oppression which they have experienced.Updates are massively made the figures are certainly not without foundation and strong roots, they dig up the scientific-scholarly Islam that had been forgotten by the Islamic people and called for re-opening the door for Ijtihad which is as closed and it was perfect. Because by the opening back door of Ijtihad will provide sufficient space to contribute to the nation and country.Various types carried by the reformer is to regrow the passion of knowledge of Islam that had been dormant, some chose to compromise with the occupiers to incorporate the ideas and ideology of Islam into the governing structure so that it can absorb and creating jobs for the Muslim citizens at a time so as to reduce unemployment. There is also a type of not colonial and choose the extreme way so that not infrequently lead to friction and war, and this is very extreme. There is also rather incorporate ideas and understand through the mass media so that can transmit the spirit and evocative Ghirah back to resistances to colonization at the time because it was very necessary.The effort already made by Islamic leaders have a lot to fruition with the resistance of the people either frontally or in the form of theoretical concept with the spirit of their country willingly colonized and trampled, causing misery for them. Once again science Islam has a very important role in uniting the spirit and the resistance to the invaders.